Association between IgG antibody levels and adverse events after first and second Bnt162b2 mRNA vaccine doses. (December 2022) - Braun, Eyal; Horowitz, Netanel A.; Leiba, Ronit; Weissman, Avi; Mekel, Michal; Shachor-Meyouhas, Yael; Hussein, Khetam; Halberthal, Michael; Azzam, Zaher S.; Berger, Gidon
Abstract: Objectives: This study sought to correlate the SARS-CoV-2 IgG antibody response level to the BNT162b2 (Pfizer BioNTech) mRNA vaccine after the first and second doses with the reported adverse events. Methods: This cohort study examined the adverse events profiles of people vaccinated with BNT162b2 in our institute between late 2020 and May 2021. Adverse events, age, and sex were reported using an electronic questionnaire, and their SARS-CoV-2 IgG antibody levels were retrieved from the hospital database. Results: Between 20 December 2020 and 31 May 2021, the adverse events questionnaire was completed by 9700 individuals who received the first vaccine dose and 8321 who received the second dose. After the first and second doses, the average antibody levels were 62.34 AU/mL (mean 4–373) and 188.19 AU/mL (mean 20–392), respectively. All of the adverse events, except local pain, were more common after the second vaccine dose. Multivariate analysis showed that after the first vaccine dose, female sex and younger age (but not IgG titres) were associated with a higher probability of adverse events (OR 2.377, 95% CI, 1.607–3.515, p = 0.000; OR 0.959, 95% CI, 0.944–0.977, p £0.000; OR 1.002, 95% CI, 0.995–1.008, p £0.601; respectively); however, all three parameters were associated with the incidence of adverse events after the second dose (OR 2.332, 95% CI, 1.636–3.322, p = 0.000; OR 0.984, 95% CI, 0.970–0.999, p £0.039; OR 1.004, 95% CI, 1.001–1.007, p £0.022; respectively). Discussion: Adverse events are significantly more common after the second BNT162b2 vaccine dose than after the first dose. We found an association between sex, age, and SARS-CoV-2 IgG antibody titre with the incidence of adverse events. Graphical abstract: Image 1